2014
DOI: 10.7897/2321-6328.02238
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol Potential of Parmotrema Species Against Colletotrichum Capsici Isolated From Anthracnose of Chilli

Abstract: Chilli is an important commercial crop and is consumed as spice as well as vegetable. Colletotrichum capsici is an important fungal pathogen causing anthracnose in chilli. The objective of the present study was to determine inhibitory activity against C. capsici of extracts of three foliose macrolichen species of the genus Parmotrema viz., P. tinctorum, P. grayanum and P. praesorediosum from Western Ghats of Karnataka, India. The antifungal effect was checked in terms of mycelial growth inhibition by Poisoned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 23 publications
(25 reference statements)
0
9
0
6
Order By: Relevance
“…The cent percent mortality of neonate larvae was observed in all neem leaf extracts prepared in water and cow urine whereas in cow urine @ 5% and 10% gave larval survival of 26.63% to 13.34%, with significantly less growth index (0.284) in comparison to untreated control (3.050). Kekuda et al, (2014) reported that the cow urine extracts of selected plants have shown inhibitory activity against mycelial growth of chilli. These formulations can be employed in the field for the control of anthracnose disease in chilli.…”
Section: Introductionmentioning
confidence: 99%
“…The cent percent mortality of neonate larvae was observed in all neem leaf extracts prepared in water and cow urine whereas in cow urine @ 5% and 10% gave larval survival of 26.63% to 13.34%, with significantly less growth index (0.284) in comparison to untreated control (3.050). Kekuda et al, (2014) reported that the cow urine extracts of selected plants have shown inhibitory activity against mycelial growth of chilli. These formulations can be employed in the field for the control of anthracnose disease in chilli.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that Parmotrema species exhibit antifungal activity against wide range of phytopathogenic fungi including seed-borne fungi (Tiwari et al, 2011;Kekuda et al, 2014;Babiah et al, 2014;Vivek et al, 2014;Devi et al, 2015;Shivanna and Garampalli, 2015). In the present study, we evaluated the antifungal potential of extract from P. tinctorum and P. cristiferum against fungi isolated from seeds of maize and ground nut by poisoned food technique.…”
Section: Resultsmentioning
confidence: 93%
“…zingiberi and Pythium aphanidermatum which cause rhizome rot disease in ginger. The study of Kekuda et al [17] revealed the marked inhibitory effect of Alpinia galanga and Pimenta dioica against mycelial growth of C. capsici. Formulations containing crude extracts from four plants with cow urine were shown to exhibit antimycotic activity against Sclerotium rolfsii [16].…”
Section: Resultsmentioning
confidence: 99%
“…Cow urine is shown to exhibit potent inhibitory activity against a wide range of pathogenic microbes including phytopathogenic fungi [3,4,[6][7][8][9][10][11]. Similarly, formulations based on cow urine and plants have shown to possess inhibitory effect against various pathogenic microorganisms [12][13][14][15][16][17]. The present study was carried out to investigate antifungal potential of cow urine extract of 14 plants collected from different places of Karnataka against two phytopathogenic fungi namely Colletotrichum capsici and Fusarium oxysporum f. sp.…”
Section: Introductionmentioning
confidence: 99%